Prototype Sistem Buka Tutup Kunci Pintu Rumah dengan Menggunakan Rfid dan Keypad 4x4 Berbasis Arduino Uno - Wiratmoko, Dedi; , Ir. Bambang Hari P., MT (2017)
RFID (radio frequency identification) is an electronic device that is modern because these tools can make it easier for us in every way in many things such as to unlock automatically. This process helps us where we did not bother using the key in general. In this study, once we provide a security system even though cuman a warning that the alarm, and here not only RFID (radio frequency identification) to access the door key in this study also use a password that is by means of 4x4 keypad and to access the door key once for anticipate if the user forgets to bring the card or the card is lost. To turn on the lights we do not need to use the switch to turn on or turn off the lights, live in spatial automatically lights will flash and the sensor used herein is a PIR sensor (Pasive Infra Red). In the making of these tools researchers conducted several experiments which do a distance measuring the extent to which the PIR sensor (Pasive Ifra Red) can capture an object, and perform measurements on RFID (Radio frequency identification) so we can find out how the maximum distance which can be reached by RFID (radio frequency identification) to read a card.